Comparative Study Between Javanese’s Kakawin Ramayana And Thai’s Ramakien As The Derivative Of Indian’s Greatest Epic Ramayana - Amalia Rachmawati (FKIP, Universitas Billfath Lamongan, 2020)
Ramayana is worldwide knowingly as the most famous and greatest Indian epic that spreading out among many countries throughout Asia such as Indonesia and Thailand. As those countries historically connected by the spreading out of Hindu religion through ancient trade. The aim of this study is to compare the Javanese’s Kakawin Ramayana and Thailand’s Ramakien of Rama I to figure out the creative process that happen in each country. Because that creative process somehow depicts socio-culture, geographic and thought of era when it’s written.